Finite element analysis and experimental study of plastic lattice structures manufactured by selective laser sintering - Sun, Wei; Choo, Hui Leng (SAGE, 2017)
The availability of additive manufacturing technologies in particular the selective laser sintering process has enabled the fabrication of high strength, lightweight and complex cellular lattice structures. In this study, the effective mechanical properties of selective laser sintering produced periodic lattice structures were investigated. Three different types of lattice structures were designed by repeating three types of open-form unit cells consisting of triangular prism, square prism and hexagonal prism. A novel approach of creating the complex and conformable lattice structures using traditional modelling software such as Creo® proposed by the authors was used. Based on the predesigned lattice structures, finite element analysis was carried out to evaluate the mechanical properties of these structures. For the experimental study, nylon samples were printed using a plastic selective laser sintering system and tested using a universal testing machine. Finite element analysis results show that lattice structures with triangular prism perform better than the other two prisms in terms of Young’s modulus to relative density ratio. Tensile tests results show good conformance with the results obtained from finite element analysis.